Preference assessment for the management of sewage sludge application on agricultural soils. (20th June 2010) - Valls, Aida; Pijuan, Josep; Schuhmacher, Marta; Passuello, Ana; Nadal, Marti; Sierra, Jordi
In this paper, the problem of managing sewage sludge disposal on agricultural soils is addressed. Sewage sludge application on agricultural soils is recommended by governments in order to recycle nutrients and organic matter. However, this managing practice may lead to ecological and human risks. In this work, we propose the use of a multi-attribute preference approach to rate and rank a set of possible soils where some defined sewage sludge could be applied. The paper is focused on the assessment of the preference value functions. The variables involved in this problem are carefully explained and different preference assessment methods are proposed according to the different nature of the variables involved. In particular, the paper explains how fuzzy expert systems could be used for modelling the interactions between sludge and soil properties.